2020
DOI: 10.3390/f11080831
|View full text |Cite
|
Sign up to set email alerts
|

Key Elements of the White-Backed Woodpecker’s (Dendrocopos leucotos lilfordi) Habitat in Its European South-Western Limits

Abstract: In the last decade, the population of the white-backed woodpecker (Dendrocopos leucotos lilfordi) (WBW) in Navarre has been reduced mainly due to the loss of suitable habitat for this species from intensive forest management, leading almost to its extinction. This study aimed to identify the key structural elements of breeding habitats of the WBW and analyze their effect on the composition of the saproxylic fungi community within the habitats. In the Special Area of Conservation, namely Quinto Real in Navarre,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Ultimately, White-backed Woodpeckers are strongly associated with mature deciduous trees and deciduous deadwood. Numerous studies from across the range have shown that reasonably large areas of unmanaged old-growth forest with a high proportion of deadwood, standing and fallen, are required for both foraging and breeding (Håland & Ugelvik 1990, Costantini & Melletti 1992, Grangé 1993, 2016, Virkkala et al 1993, Hogstad & Stenberg 1994, Bernoni 1995, Mikusiński & Angelstam 1998a, 1998b, Frank 2002, Håpnes 2003, Melletti & Penteriani 2003, Pavelka 2003, Garmendia et al 2006, Czeszczewik 2009, Gerdzhikov et al 2018, Schwaiger & Lauterbach 2019, Urkijo-Letona et al 2020, Bühler 2021. In Hungary, the species generally only occurs in hill forests where there are native deciduous tree species older than 60-70 years and a minimum volume of 20 m 3 /ha of deadwood (Szmorad et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, White-backed Woodpeckers are strongly associated with mature deciduous trees and deciduous deadwood. Numerous studies from across the range have shown that reasonably large areas of unmanaged old-growth forest with a high proportion of deadwood, standing and fallen, are required for both foraging and breeding (Håland & Ugelvik 1990, Costantini & Melletti 1992, Grangé 1993, 2016, Virkkala et al 1993, Hogstad & Stenberg 1994, Bernoni 1995, Mikusiński & Angelstam 1998a, 1998b, Frank 2002, Håpnes 2003, Melletti & Penteriani 2003, Pavelka 2003, Garmendia et al 2006, Czeszczewik 2009, Gerdzhikov et al 2018, Schwaiger & Lauterbach 2019, Urkijo-Letona et al 2020, Bühler 2021. In Hungary, the species generally only occurs in hill forests where there are native deciduous tree species older than 60-70 years and a minimum volume of 20 m 3 /ha of deadwood (Szmorad et al 2018).…”
Section: Introductionmentioning
confidence: 99%